PENGARUH KITAB ARAB MELAYU TERHADAP PEMBINAAN AKHLAK TA’DZIM SANTRI KEPADA GURU DI TPA AS-SA’ADAH LAMGUGOB - Fauzan Azima Fauzan Azima; Ainal Mardhiah Ainal Mardhiah; Mashuri Mashuri (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2024)
This paper aims to find out the teaching sources and teaching materials for moral education in the formation of students‘ daily morals, explain the implementation of moral education, and want to know the supporting and inhibiting factors for the implementation of moral education in the formation of students’ daily morals. With these objectives, it is obtained that the point about the formation of santri morals is taken from several classical books, namely the Arabic Malay Akhlak book. Teaching materials related to daily morals are taken from the Arabic Malay Akhlak book. The supporting factors for the formation of santri morals are religious learning activities, adequate facilities, the enthusiasm of ustadz/ustadzah and students, a comfortable environment and there are santri rules that must be obeyed. Apart from supporting factors, there are inhibiting factors, namely the influence from outside the tpa.